Sedentary patterns and health outcomes in the oldest-old: a latent profile analysis - Lebuf, Elien; Van Dyck, Delfien; Van de Velde, Laura; Beeckman, Melanie; Van Cauwenberg, Jelle; Compernolle, Sofie (PeerJ, 2024)
Background Sedentary behavior is most prevalent among those aged 80 years and above, referred to as the oldest-old. Current literature emphasizes the significance of sedentary behavior patterns, but further evidence is required to understand how these patterns relate to specific health outcomes and to identify at-risk profiles for tailored interventions in the oldest-old. Therefore, the aim of this study was to identify profiles of adults aged 80+ years based on their sedentary patterns and health outcomes, and to examine associations between profiles and socio-demographics. Methods A cross-sectional study was conducted in Flanders (Belgium) from February 2021 to December 2022 recruiting 90 older adults (80+) through convenience sampling, employing word of mouth, social media and local service centers. Latent profile analysis identified device-based sedentary patterns and assessed their associations with physical and cognitive functioning, mental health-related quality of life (QoL), and social isolation. Associations of these profiles with socio-demographic factors were analyzed. Results Three distinct profiles were identified: (1) the ‘cognitively and physically frail’ profile, (2) the ‘healthy’ profile and (3) the ‘lower mental health-related QoL’ profile. Those in the ‘cognitively and physically frail’ profile exhibited the least favorable sedentary pattern, and had a higher likelihood of residing in a nursing home. No significant differences were found for the other socio-demographic variables, being age, sex, educational degree and family situation. Conclusions Three distinct profiles in the oldest-old population, based on cognitive and physical functioning, mental health-related QoL, and sedentary behavior patterns, were identified. Lower physical and cognitive functioning was associated with unhealthy sedentary patterns. Further research with larger samples is crucial to uncover potential links between socio-demographics and at-risk subgroups, enhancing our understanding of sedentary behavior and geriatric health outcomes in this population.
Keywords: Elderly; Sitting; Physical health; Mental health; Typologies; Sedentary behavior